1992
DOI: 10.1897/1552-8618(1992)11[503:tuofas]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Freshwater and Saltwater Animals to Distinguish Between the Toxic Effects of Salinity and Contaminants in Irrigation Drain Water

Abstract: Irrigation drain waters entering Stillwater Wildlife Management Area (SWMA) in south‐western Nevada contain elevated levels of salinity and several inorganic contaminants (As, B, Cu, Li, Mo, and Sr). Mortalities of fish and waterfowl at the management area are believed to be associated with the poor water quality of the drains. The objective of the present study was to use fresh‐water and saltwater animals to distinguish between the toxic effects of salinity and contaminants in effluent samples collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…The drainage was highly toxic, causing mortality within 96 hr (59). Reconstituted water formulated to resemble surface water from Stillwater NWR, but without the complement of trace element contaminants (e.g., As, B, Cu, Li, MO, Sr), was toxic to salt-tolerant organisms (60). However, the level of toxicity increased in samples that also included trace elements at concentrations normally found in the drainage.…”
Section: Stillwater Refuge Toxicity Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The drainage was highly toxic, causing mortality within 96 hr (59). Reconstituted water formulated to resemble surface water from Stillwater NWR, but without the complement of trace element contaminants (e.g., As, B, Cu, Li, MO, Sr), was toxic to salt-tolerant organisms (60). However, the level of toxicity increased in samples that also included trace elements at concentrations normally found in the drainage.…”
Section: Stillwater Refuge Toxicity Studiesmentioning
confidence: 99%
“…The results indicated that salinity, contaminants, and atypical ratios of major ions (e.g., sulfate, magnesium, chloride, sodium, etc.) all acted together to cause the observed toxicity; no single contaminant or water-quality variable was responsible (59,60).…”
Section: Stillwater Refuge Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt toxicity for daphnia magna ranges from 0.6-1 %. 5,6 Since the ceriodaphnia are typically more sensitive than daphnia magna, their tolerance to salt would be less. Open literature has shown that the sensitivity to sodium chloride between daphnia magna and ceriodaphnia dubia differ by approximately 50% (ceriodaphnia being more sensitive).…”
Section: Introductionmentioning
confidence: 99%
“…O monitoramento ecotoxicolôgico, entre outras aplicações, contribui no estabelecimento de critérios de qualidade de águas e sedimentos de modo a proteger a biota aquática, no monitoramento de efluentes industriais e áreas de influência, como também na avaliação da eficiência de sistemas de tratamento (USEPA, 1989;USEPA, 1991b Baseado em trabalhos como BOELTER et al (1992), DWYER et al (1992) e INGERSOLL et al (1992, DICKERSON et al (1996) apresenta um modelo para previsão dos efeitos para C. dúbia a partir da concentração dos oito principais íons. Tal modelo, baseado em uma regressão logística multivariada foi aplicado em 22 sítios de 4 estados norte-americanos.…”
Section: Avaliação Dos Efeitos De Misturas Complexas No Ambienteunclassified